Multinational Enterprises, International Trade, and Productivity Growth : Firm-Level Evidence From the United States - Yeaple, Stephen (IMF Working Papers; Working Paper, 2003)
We estimate international technology spillovers to U.S. manufacturing firms via imports and foreign direct investment (FDI) between 1987 and 1996. In contrast to earlier work, our results suggest that FDI leads to substantial productivity gains for domestic firms. The size of FDI spillovers is economically important, accounting for about 11 percent of productivity growth in U.S. firms between 1987 and 1996. In addition, there is some evidence for import-related spillovers, but it is weaker than for FDI spillovers. The paper also gives a detailed account of why our study leads to results different from those found in previous work. This analysis indicates that our results are also likely to apply to other countries and periods.